THE IMPACT OF THE NON-OIL AND GAS SECTOR'S TAX REVENUE ON ECONOMIC GROWTH IN INDONESIA - Anita Putri Giantoro (SEAN Institute, 2023)
Economic growth is a long-term economic problem that must be faced by every country, including Indonesia. National development and economic growth are two tings that cannot be separated, because national development is carried out to support people's economic activities and increase the rate of economic growth. Tax revenue, especially from income tax, is currently the largest source of state revenue. Therefore researchers want to conduct research on the impact of the non-oil and gas sector tax revenue on economic growth, with the object of research being Value Added Tax (VAT), Corporate Income Tax (CIT), Final Income Tax, Customs Tax (CED), and certain Building Land Tax as independent variables, and Economic Growth as measured by Gross Domestic Product at constant prices as the dependent variable. This research is a clausal study research, quantitative method, research instrument in the form of financial report data from the Ministry of Finance for the last 8 years, namely from 2013 to 2020. The results of this study show that VAT, PPhB, PPhF, PBC, and PBB-P3 receipts are the same. equally positive effect on economic growth in Indonesia. This can be seen from the significant results of each variable. VAT has a significant value (0.0248), CIT (0.0010), Final Tax (0.0051), CED (0.0000), and Building Land Tax (0.0196). So it can be concluded that tax revenues from the non-oil and gas sector have a positive effect on economic growth in Indonesia. equally positive effect on economic growth in Indonesia. This can be seen from the significant results of each variable. VAT has a significant value (0.0248), CIT (0.0010), Final Tax (0.0051), CED (0.0000), and Building Land Tax (0.0196). So it can be concluded that tax revenues from the non-oil and gas sector have a positive effect on economic growth in Indonesia. equally positive effect on economic growth in Indonesia. This can be seen from the significant results of each variable. VAT has a significant value (0.0248), CIT (0.0010), Final Tax (0.0051), CED (0.0000), and Building Land Tax (0.0196). So it can be concluded that tax revenues from the non-oil and gas sector have a positive effect on economic growth in Indonesia.